Low maternal serum pregnancy-associated plasma protein-A as a risk factor of preeclampsia - Suchaya Luewan (2018)
© 2018, Singapore Medical Association. All rights reserved. INTRODUCTION Low levels of pregnancy-associated plasma protein-A (PAPP-A) might be associated with abnormal placentation, leading to the development of preeclampsia during late gestation. We aimed to determine the association between low serum PAPP-A levels and rates of preeclampsia in Thai women with otherwise low-risk pregnancies. METHODS A cohort study was conducted on consecutive singleton pregnancies undergoing first trimester screening for fetal Down syndrome at a tertiary centre hospital. A prospective database was assessed for patient records, including PAPP-A levels, pregnancy outcomes and obstetrics complications. Pregnancies with potential causes of preeclampsia were excluded. Enrolled women were categorised into two groups: women with normal PAPP-A levels (≥ 10th percentile; control group); and those with low PAPP-A levels (< 10th percentile; study group). The main outcome measure was rate of preeclampsia. RESULTS Of 6,887 women screened, 3,830 were available for analysis and 167 were excluded due to potential confounders. Of the remaining 3,663 women enrolled, 357 women were categorised as having low PAPP-A levels and 3,306 had normal PAPP-A levels. The prevalence of preeclampsia (8.4% vs. 2.6%) and early-onset preeclampsia (i.e. before 34 weeks of gestation) (1.1% vs. 0.1%) was significantly higher (relative risk 3.27 and 9.26, respectively) in women from the study group than in the control group. CONCLUSION Pregnancy with PAPP-A levels < 10th percentile was significantly associated with an increased risk of preeclampsia that tended toward early development. Therefore, pregnant women with low PAPP-A levels in the first trimester should be considered to be at increased risk of preeclampsia.